LITERASI SAINS PADA PEMBELAJARAN MENULIS ESAI BERMETODE SAKERA DALAM PEMBELAJARAN BAHASA INDONESIA - Yuanita Widiastuti (Kalam Nusantara Institute, 2023)
The aim of the research is to describe the application of the Sakera method in learning Indonesian on essay material containing scientific literacy and to describe the implications in the form of increasing literacy. The method used in the researchis descriptive qualitative. The research results show that the Sakera method is a new breakthrough in learning methods. Thisinnovation can be carried out by Indonesian language subject teachers easily and pleasantly. The sakera method positions teachers as facilitators in learning who have strong, innovative and sustainable efforts so as to change learning methods that refer to the large domain of scientific literacy, namely the science process. In the era of independence, learning with the dimension of the Pancasila student profile, namely critical reasoning, stands out in this innovation. Another skill aspect that has implications is the writing aspect. Scientific literacy exists as a real form of innovation that can be demonstrated.